2010
DOI: 10.1603/en09316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Population Growth ofRhynchophorus ferrugineus(Coleoptera: Curculionidae) on Sugarcane

Abstract: The effect of temperature on the developmental time, survival, and reproduction of Rhynchophorus ferrugineus (Olivier) reared on sugarcane was studied at seven constant temperatures (16, 20, 24, 28, 32, 36, and 40 degrees C). The developmental threshold temperatures and effective accumulated temperatures for the whole generation were 17.41 degrees C and 1,590.72 DD, respectively. One generation had the highest survival rate (26.67%) at 28 degrees C. The egg failed to survive at 16 and 40 degrees C. The populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
5
21
1
Order By: Relevance
“…The optimal temperature was 27 °C, which is consistent with the principal distributions of R. ferrugineus in China. We also found that R. ferrugineus was unable to complete development at 15 and 18 °C; this observation is consistent with the report by Li et al 14 that this species cannot complete development and reproduction at 16 °C (or 40 °C) on sugarcane and that the threshold temperature for egg hatching is 18.28 °C. Similarly, Zhao and Ju29 reported a survival rate for the generation of R. ferrugineus of only 10.0% at 19 °C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The optimal temperature was 27 °C, which is consistent with the principal distributions of R. ferrugineus in China. We also found that R. ferrugineus was unable to complete development at 15 and 18 °C; this observation is consistent with the report by Li et al 14 that this species cannot complete development and reproduction at 16 °C (or 40 °C) on sugarcane and that the threshold temperature for egg hatching is 18.28 °C. Similarly, Zhao and Ju29 reported a survival rate for the generation of R. ferrugineus of only 10.0% at 19 °C.…”
Section: Discussionsupporting
confidence: 93%
“…To date, the thermal requirements and the lower temperature thresholds for development, oviposition, and egg hatching in R. ferrugineus have been described512 along with effects on emergence13 and population growth14. However, there is limited information on how temperature affects population demographics and age- and stage-specific traits, which are important for metamorphic insects15.…”
mentioning
confidence: 99%
“…The predicted number of eggs laid in the next generation was determined by the number of female adults in the previous generation and the number of eggs per female. Using the methods of Tao et al (2008) and Li et al (2010), the population trend index (I) of T. rufivena was calculated as the expected number of eggs in the next generation divided by the initial number of eggs.…”
Section: Experimental Population Life Tablesmentioning
confidence: 99%
“…The predicted number of eggs laid in the next generation was determined by the number of female adults in the previous generation and the number of eggs per female. The population trend index (I) was calculated as the expected number of eggs in the next generation divided by the initial number of eggs (Tao et al 2008;Li et al 2010). Based on the analysis of the population trend index (I), we concluded that 28 °C was the optimum temperature.…”
Section: Experimental Population Life Tablesmentioning
confidence: 99%
“…For example, the paper of Leefmans (1920) cited by Dembilio and Jacas (2012) mentioned that 87% of hatchability was reported when females reared on sago pump lumps and 65-95% of hatchability was obtained when females reared on sugarcane (Aldhafer et al 1998). Li et al (2010) reported that the temperatures from 28 to 32°C were the most suitable temperatures for the development time, survival and reproduction of RPW reared on sugarcane. In the present study, the laboratory temperature conditions was 25±2°C, which may suggest that the temparature condition might be affecting the fecundity and fertility rate for this experiment.…”
Section: Resultsmentioning
confidence: 99%